1970
DOI: 10.1039/df9705000182
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation in GeO–GeO2glasses

Abstract: A series of transparent homogeneous amorphous solids between Ge02 and GeO has been prepared by rapid quenching of liquids and by vapour deposition. Density and refractive index increase smoothly with increasing Ge/O ratio and provide a useful index of composition. Glasses in the range GeO-GeOlS8, undergo a rapid exothermic transformation when heated above 400°C accompanied by a pronounced blackening, an increase in refractive index, and a slight decrease in density. Electron microscopy and diffraction results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…On the other hand, the temperature rise by a single light pulse can be estimated very roughly as DT % Q/ {c(a À1 + L t )} [29], where Q is absorbed pulse energy per unit area, c is the specific heat per unit volume [30], a À1 (%200 nm) is the penetration depth of excitation light, and L t (%70 nm) is the thermal diffusion length, which is written down as 2(js/c) 1/2 , where j is the thermal conductivity [31] and s (%10 ns) is the pulse duration. This estimation gives, for the present condition of Q % 40 mJ/cm 2 , DT % 400 K, which cannot be neglected since the glass-transition temperature of GeO 2 films is reported to be $360°C [21]. However, as shown in Fig.…”
Section: Microscopicmentioning
confidence: 90%
See 1 more Smart Citation
“…On the other hand, the temperature rise by a single light pulse can be estimated very roughly as DT % Q/ {c(a À1 + L t )} [29], where Q is absorbed pulse energy per unit area, c is the specific heat per unit volume [30], a À1 (%200 nm) is the penetration depth of excitation light, and L t (%70 nm) is the thermal diffusion length, which is written down as 2(js/c) 1/2 , where j is the thermal conductivity [31] and s (%10 ns) is the pulse duration. This estimation gives, for the present condition of Q % 40 mJ/cm 2 , DT % 400 K, which cannot be neglected since the glass-transition temperature of GeO 2 films is reported to be $360°C [21]. However, as shown in Fig.…”
Section: Microscopicmentioning
confidence: 90%
“…The deposition was carried out in pure Ar gas with a pressure of $4 Pa at a growth rate of $15 nm/min. A compositional ratio between Ge and O in the film could be estimated at GeO 1.8 from comparing a measured refractive index of $1.7 to previous results [17,21]. In the present work, however, the composition is denoted as GeO 2 for simplicity.…”
Section: Methodsmentioning
confidence: 97%
“…2 shows estimated compositions of the samples, with color symbols corresponding to the appearance in Fig. 1, and reported glass-forming regions on the Ge-S and Ge-O axes [17,18]. In this triangle, xGeO 2 -(100 À x)GeS 2 compositions should be located on a tie line connecting GeS 2 and GeO 2 .…”
Section: Methodsmentioning
confidence: 98%
“…It was found that increase in the portion of GeO in the system caused the growth of refractive index and density that was followed by the decrease in glass transition temperature (Fig. 6) [42]. One can conclude that, the growth of refractive index is connected with the structure densifying because polarizability estimated through the Lorentz-Loretz formula was found to be constant.…”
Section: Explanation Of Dispersion In Geo 2 Propertiesmentioning
confidence: 96%
“…Authors of [42] supposed that the structural peculiarities of vGeO 2 originated from the presence of two-valence Ge impurity. This model explains the observed irreproducibility of the data in Table 1.…”
Section: Explanation Of Dispersion In Geo 2 Propertiesmentioning
confidence: 99%